Интересная находка самца рода гипоаспис — Hypoaspis Canestrini (Acarina, Gamasoidea) - Щербак, Г.И. (Вестник зоологии, 1973)
Description and drawings are given of the male mite of Hypoaspis genus, Cosmolaelaps subgenus with an unusual for Gamasoidea chitin process on the sternitogenitoventral shield. The length of the process is 0.08 mm.